Epidemiology and healthcare burden of implant-associated complications in Germany: a nationwide population-based analysis - Houmam Anees; Christian Heiss; Thaqif El Khassawna (European Journal of Trauma and Emergency Surgery, 2026)
Abstract Purpose Implant-associated complications remain a major challenge in orthopaedic and trauma surgery, particularly among elderly patients requiring revision procedures or infection management. This study analysed nationwide trends and healthcare burden of implant-associated complications in Germany. Methods Nationwide German hospital discharge data from 2000 to 2023 were analysed and complemented by Diagnosis-Related Group (DRG) data from 2024. Cases were identified using ICD-10-GM code T84 and its subcategories. Outcomes included temporal trends, age-standardised incidence, demographic characteristics, in-hospital mortality, length of stay (LOS), and DRG-based healthcare resource utilisation. Results Hospitalisations for implant-associated complications increased from 45,121 in 2000 to a peak of 95,154 in 2011, followed by a decline to 72,846 in 2023. Age-standardised incidence decreased by approximately 31% between 2010 and 2023. Segmented regression identified a temporal breakpoint in 2010.6, with annual percentage changes of + 6.21% before and − 3.55% after the breakpoint. Annual hospitalisations for periprosthetic joint infection increased from 5,367 to 11,215, while osteosynthesis-associated infections increased from 2,469 to 7,059. Mean LOS decreased from 20.8 to 11.8 days, whereas in-hospital mortality remained stable. Compared with low-complexity cases, infection-related complications were associated with prolonged hospitalisation and approximately threefold higher treatment costs, while complex revision procedures generated mean costs exceeding €9,000 per case. Conclusion Although the age-standardised incidence of implant-associated complications has declined in recent years, infection-related complications and complex revision procedures continue to impose a substantial clinical and economic burden, underlining the need for continued optimisation of prevention and treatment strategies.